Buck-boost inverter using single phase matrix converter topology / Mohd Shafie Saharuddin - Saharuddin, Mohd Shafie (2010)
The aim of this project is about a buck-boost inverter using Single Phase Matrix Converter topology. The main attribute of the new inverter topology is the fact that it generates an AC output voltage larger or smaller than the DC input one, depending on the instantaneous duty cycle or modulation index (MI). It works in implementation of buck-boost inverter by using Single Phase Matrix Converter (SPMC). The inverter can handle a wide range of DC input voltages and produce a fixed AC output voltage. The Sinusoidal Pulse Width Modulation (SPWM) used to synthesis the output waveform. An improved SPWM control method employing DC bias sine modulation wave is presented to optimize the inverter performance. Prior to its practical realization a computer simulation model is developed to investigate the behavior of the SPMC using Matlab/Simulink (MLS). An experiment Test-Rig was constructed to verify the operation. The XILINX FPGA schematic design was used for digital control implementation. Selected simulations and experimental result are presented to verify proposed operation.